Inclusive Politics For Persons With Disabilities: Gus Dur’s Experience in Building Inclusive Democracy in Indonesia - Abdullah Fikri (Veteran Justice Journal, 2021)
Abstract Many believe that the reformation era of Indonesia, in the post of 1998 political upheaval, has brought Indonesia to be a democratic country, where all citizens disregard their gender, ability, ethnicity and religious status, enjoy freedom, equal right and social justice. People with disabilities is one of the groups experiencing discrimination and marginalization in Indonesia's social and political domain. While this situation continues to happen until now, the reformation era has been seen as opening the door for people with disabilities to start voicing their aspirations and enjoy wider social and political participation. Drawing from the political career of Abdurahman Wahid, widely known as Gus Dur, this paper argues that despite the promise of democracy, the position of people with disabilities in Indonesia's political context is not necessarily secure. The presidential election 1999 and 2004 followed by the 2008 election bill showed that disability was a bargaining chip for political position; it was defined differently according to the political interest of political parties. The election of Gus Dur as president in 1999 was due to the acceptance of political parties widely known as Central Poros -- as Gus Dur supporters --toward his “disability”. Such an inclusive democracy was then shattered in the 2004 election when Gud Dur's visual impairment was seen as his inability to meet the requirement of physically and mentally health (physically and mentally health), one of the eligibility for candidacy. Gus Dur was not re-elected. Such a rejection toward Gus Dur's disability lead and his team to advocate disability issue in Indonesian political policies and practices. The result is the 2008 election policy which formally stated that disability is not supposed to be seen as physical or mental condition incompatible with the criteria of physically and mentally healthy .The paper argues that democratic and political inclusion can never be achieved without the right understanding of disability, as well as the legal guarantee of political and social right of person with disability in Indonesia political sphere. Keywords: Disability; Politic Democracy; Inclusive; Law